Нематоди родини HETERODERIDAE SCARBILOVICH, 1947 та принципи контролю їх чисельності в біогеоценозах України - Бабич, Анатолій Григорович (НУБіП України, 2021)
Дисертація на здобуття наукового ступеня доктора біологічних наук зі спеціальності 06.01.11 «Фітопатологія». Національний університет біоресурсів і природокористування України. Київ, 2021. Теоретично обґрунтовано, експериментально підтверджено, узагальнено та представлено системний підхід до вивчення седентарних фітопаразитичних нематод родини Heteroderidae, а також розроблення сучасного нематологічного моніторингу та екологічно безпечних заходів їх фітосанітарного контролю. За період проведення наукових досліджень виявлено 12 видів цистоутворюючих нематод. Найбільших збитків завдають: бурякова, вівсяна, золотиста картопляна й хмельова нематоди. За накопичення високої чисельності втрати врожаю багаторічних бобових трав зумовлюють: конюшина і люцернова цистоутворюючі нематоди. Розроблений цистовиділювач для аналізу бульбо- та коренеплідної продукції забезпечує в 1,5–3 рази вищу ефективність виявлення цист у досліджених зразках, порівнюючи з базовим пристроєм. Розподіл цистоутворюючих нематод за вертикальним профілем, насамперед, залежав від глибини залягання родючого шару, способів його обробітку, видового складу фітонематод і вирощування певних рослин- живителів. Основними джерелами пасивного розселення цистоутворюючих нематод є вітрова ерозія, садивний матеріал, засоби механічного обробітку ґрунту. У природних фітоценозах розселення цистоутворюючих нематод здебільшого відбувається факультативно ґрунтозаселяючими і землериючими тваринами. Для запобігання їх масового накопичення максимальна насиченість сівозмін рослинами-живителями не має перевищувати: зерновими колосовими – 40 %, картоплею – 20 % (10 % сприйнятливі + 10 % глободерозостійкі), багаторічними бобовими травами – 30 % (посіви під покривом зернових колосових + багаторічні бобові одно-дворічного використання). Поєднання імунологічного методу із застосуванням метаболічних препаратів поліфункціональної дії (фітозахисної, рістрегулювальної, адаптогенної) забезпечувало вищу ефективність біологічного очищення ґрунту від золотистої картопляної нематоди, порівнюючи з використанням лише стійких сортів картоплі
Dissertation for the degree of Doctor of Biological Sciences majoring in 06.01.11 «Phytopathology». National University of Life and Environmental Sciences of Ukraine. Kyiv, 2021. A systematic approach to the study of sedentary phytoparasitic nematodes of the family Heteroderidae, the development of modern nematological monitoring and environmentally safe measures for their phytosanitary control has been theoretically justified, experimentally studied, generalised, and presented. During the research period, 12 species of heteroderids were recorded. Currently, the economically significant species are as follows: sugar beet cyst nematode, oat cyst nematode, golden potato and hop cyst nematode. Clover and alfalfa cyst nematodes are species of economic importance for perennial legumes. In order to identify heteroderids, it is advisable to use an enhanced key to determine their species composition. Our assessment of biochemical and PCR testing proved their efficiency, however, due to the high cost of modern diagnostics methods, we consider it advisable to use them primarily to determine the species composition of novel and quarantine species of nematodes. The optimal dates for conducting aerial monitoring of phytocoenoses for heteroderids’ infestation are the last decade of June, the first-second decade of July. The use of pyramidal or conical-shaped inserts during soil biotesting increased the probability of detecting nematode species in low population densities which are the most complicated for diagnostics. High reliability of biotesting in the field environment was achieved due to compliance with the technological guidelines of plant cultivation that are similar with commercial production ones. Using of developed cyst separator for analysis of tuber and root crops provided 1.5–3 times higher efficiency of detection of cysts in comparison with the basic device. The distribution of cyst nematodes by the vertical profile of the soil primarily depended on the depth of the fertile layer, the methods of soil tillage, the species composition of phytonematodes and the type of host plants. The main sources of passive dispersal of cyst nematodes are wind erosion of the soil, sort of planting material, and mechanical tillage type. In natural phytocoenoses, the dispersal of heteroderids occurs optionally by ground-digging animals and soil-dwelling insects. Various modifications of the dormant state and high ecological adaptability to endure adverse conditions ensure the survival of species for up to ten-year breaks between the re-cultivation of host plants. To avoid high population of heteroderids, the maximum saturation of crop rotations with host plants should not exceed: cereal grains – 40 %, potatoes – 20 % (10 % susceptible + 10 % globodera-resistant varieties), perennial legumes – 30 % (crops under the cover of cereal grains + perennial legumes – one-two years of vegetation). Polyfunctional products based on secondary metabolites for pre-sowing seed treatment should be used on condition that the initial cyst nematodes population in the soil does not exceed the economic thresholds of harmfulness more than three times. The combination of the immunological method with the use of compounds based on secondary metabolites with multifunctional effect (plant defence, growthstimulating, stress response-enhancing) provides higher efficiency of biological soil clean-up from golden potato cyst nematode in comparison with the exclusive use of resistant solanaceous crops varieties
Keywords: цистоутворюючі нематоди; ідентифікація; джерела розселення; фенологія; кількість генерацій; рівні шкідливості; поліфункціональні метаболічні препарати; моніторинг; фітосанітарний контроль; cyst nematodes; identification; sources of distribution; phenology; number of generations; levels of harm; compounds based on secondary metabolites with multifunctional effect